Narrative Art Therapy to Increase Hope in Young People with Psychotic Disorder: A Single Case Experimental Design - Rosada Dwi Iswari; Nida Ul Hasanat (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Psychotic disorders are severe mental illnesses that cause distress and hopelessness for individuals who experience them. However, hope marks the beginning of psychological recovery from a psychotic disorder. This study aims to explore the role of narrative-approach art therapy in increasing hope for young people with psychotic disorders. The research was conducted using an A-B-A single-case design. Participants were recruited based on the following criteria: (1) psychotic outpatients currently in the recovery phase, (2) adolescents or young adults aged between 15-30 years, (3) able to communicate, and (4) consenting to participate in the research. The Hope Scale and daily hope condition were used to measure the level of hope three times, namely before, during, and follow-up. Visual inspection indicates that there was an increase in hope after the intervention, both on the Hope Scale and in the average score of daily hope condition. Two participants showed a sustained impact up to two weeks following the intervention, while the remaining participant experienced a decrease in hope during the follow-up. Factors that could potentially influence these results will be discussed. This study provides evidence of the feasibility of narrative art therapy for individuals with psychosis.